Estrategias de lucha contra la pobreza en América Latina. Análisis crítico de los planteamientos de algunos organismos internacionales - Boltvinik, Julio (El Colegio de México A.C., 1998)
This is a critical analysis of the proposals for estimating poverty and of the policies for struggling against it presented by organisms such as the World Bank (wb) and the Economic Commission for Latin America (cepal), which sometimes contrast with the criteria of unpds (United Nations Development Program) Regional Proyect for Overcoming Poverty. The article first classifies the different ways these organisms measure poverty, which result in quite dissimilar data of its ocurrence in Latin America, and then, regarding the policies for struggling against this situation, defines their sense and context for each organism (the neoliberal model for wb, an "integrated approach" for cepal, and "development without poverty" for unpd). The author then refers to how the three organisms explain the existence and sharpening of poverty, and later details the goals and elements of their strategies (sustainable reduction for wb; equal environmentally sustainable and democratic growth for cepal; and greater life quality and quantity for the members of society, for unpd). The work ends with a comparative and critical balance of the basic traits, particularly the proposals of wb and cepal, showing both their differences and common points.